Design and extreme structural analysis of wind turbine blades: Beam and shell model comparison and discussion for a 10-MW reference turbine - de Almeida, Isadora Toledo; Lapa, Gabriel Vicentin Pereira; Gay Neto, Alfredo; de Almeida, Sérgio Frascino Müller [UNESP] (Elsevier, 2025)
The progressive growth of wind turbine blades requires lightweighting to ensure aerodynamic performance. However, gaps in the comprehension of failure mechanisms, such as trailing edge buckling, lead to non-scalable experimental-based optimization frameworks. Nonlinear finite element methodologies are now central in blade design, giving insight into the structural behavior and speeding up design iteration. This work aims to examine finite element techniques from the standpoint of the DTU 10-MW reference wind turbine. The geometrically nonlinear anisotropic beam model is verified against its corresponding layered shell model for the reference turbine, followed by a comparison between linear and nonlinear stability methodologies for buckling strength assessments. The discussion on stability highlights the eminence of including nonlinear methods to account for shells’ typical imperfection sensitivity in blade design routines.
Keywords: Composite beam; Composite shell; Imperfection-sensitivity; Nonlinear buckling; Nonlinear FEM; Trailing edge buckling; Vibration method; Wind turbine blade